Actinidia callosa peel (kiwi fruit) ethanol extracts protected neural cells apoptosis induced by methylglyoxal through Nrf2 activation. (May 2014) - Lee, Chia-Chen; Lee, Bao-Hong; Wu, She-Ching
Abstract Context: Methylglyoxal (MG) is a reactive dicarbonyl compound generated as an intermediate of glycolysis during the physical glycation in the diabetic condition. MG itself has been commonly implicated in the development of diabetic neuropathy. Several active compounds in Actinidia callosa have been found to inhibit glycation and MG-protein reaction. Objective: This study investigated the protective effects of A. callosa (kiwi fruits) peel ethanol extracts (ACE) on MG-induced Neuro-2A cell apoptosis. Materials and methods: The Neuro-2A cells pre-treated by ACE (50–200 μg/mL) or allyl-isothiocyanate (AITC) (50 μM) for 6 h, in turn, the cells were treated with MG (250 μM) for 24 h. Results: ACE or AITC treatment markedly inhibited the generation of reactive oxygen species (ROS) and the elevation of caspase-3 and capase-9 levels induced by MG in Neuro-2A cells. ACE and AITC elevated Bcl2 and inhibited Bax expressions in MG-induced Neuro-2A cells. ACE elevated Nrf2 transcriptional activity and nuclear translocation in MG-induced Neuro-2A cells. Nrf2 down-stream molecules including HO-1 and GCL were elevated by ACE or AITC treatment in MG-induced Neuro-2A cells. The protective effects of ACE on MG-induced Neuro-2A apoptosis were attenuated while Nrf2 knockdown. Discussion and conclusion: We established the first evidence that ACE might contribute to the prevention of the development of diabetic neuropathy by blocking the MG-mediated intracellular glycation system.